Effects of surfactants on hydrodynamics and mass transfer in a co-current downflow contacting column - Orhan, Ramazan; Dursun, Gulbeyi (Inst Chemical Engineers, 2016)
The effects of liquid properties on gas hold-up, bubble formation and mass transfer in a co-current downflow contacting column (CDCC) were investigated using tap water and different types surfactant solutions. The experiments were conducted using various orifice diameters (2,3 and 4 mm) and at different superficial gas velocities (0.07-0.188 ms(-1)) and liquid re-circulation rates (3.3-6.67 x 10(-5) m(3) s(-1)). Gas hold-up and volumetric mass transfer coefficient increased with increasing superficial gas velocity and liquid flow rate. As the surface tension decreased so did the size of the bubbles formed such that low it a values and higher gas hold-up values were obtained. Empirical correlations were proposed for evaluating gas hold-up and volumetric mass transfer coefficients as a function of liquid kinetic power per liquid volume in the column, superficial gas velocity and relative surface tension using the experimental data obtained for the different types of surfactant solutions. These proposed correlations fit the experimental data of gas hold-up and mass transfer coefficients reasonably well for all gas and liquid flow rates and at orifice diameter used. (C) 2016 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Co-current down flow; Mass transfer; Gas hold-up; Surfactant